Utilization of Social Commerce and Social Proof Marketing on Business Performance of Micro, Small and Medium Enterprises - Ade Titi Nifita; Husni Hasbullah; Ade Perdana Siregar (Dinasti Publisher, 2022)
The shift in consumer consumptive patterns has experienced a shift from shopping at conventional stores to online vendors or stores, this is in line with the current development of e-commerce. Social media provides enormous benefit opportunities for MSMEs in improving business performance. The integration of social media, social networking sites and e-commerce if viewed from the substantial growth caused by social e-commerce. In the process of selecting alternative products to consumers, especially Jambi Batik products, the dominant consideration is social proof. The objectives of this study are (1) to examine the effect of social commerce on the business performance of MSMEs; (2) To examine the effect of social commerce on social proof marketing; (3) Assessing the effect of social proof marketing on MSME business performance; (4) Assessing the role of social proof marketing in mediating the influence of social commerce on MSME business performance. The data analysis method used is Structural Equation Modeling (SEM) measurements using SmartPLS software. The results of the study show that (1) Social commerce shows a significant positive effect on business performance, it is proven that the higher the social commerce in a business, the business performance will increase; (2) Social commerce shows a significant positive effect on social proof, it is proven that the higher the social commerce in a business, the better the social proof; (3) Social proof shows a significant positive effect on business performance, it is proven that the better social proof in a business, the business performance will increase; (4) Social proof as a mediation of the influence of social commerce has a significant positive effect on business performance, where social proof is considered a variable that strengthens social commerce in improving business performance.